Real Interest Rates, Bubbles and Monetary Policy in the GCC countries - E. M. Bentour; W. A. Razzak (Economics and Econometrics Research Institute (EERI), 2010)
The Gulf Cooperation Council countries (GCC) include Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and the UAE. Their monetary policy objective is to stabilize the foreign price, i.e., exchange rate instead of the domestic price level, where the nominal interest rate is equalized with the US federal fund rate, but the inflation rates are independent. High oil prices and the depreciating US dollar caused inflation to rise and real interest rates to be persistently negative in the UAE and Qatar. Asset prices bubbles formed then burst creating large loses. They could have moderated the effect of, or avoided, the bubble had they floated the currency and stabilized domestic prices.
Keywords: E31; E37; E58; 330; Inflation; real interest rate; bubbles